"Just Because I'm a Lesbian Doesn't Mean I'm Evolved" The "Bad Queer" Women's Comedic Web Series - San Filippo, Maria (Velvet Light Trap, 2020)
The queer women's comedic web series that have flourished in the last decade, serving as launching pads for their creators, coincided with media-industry nichification's segmentation of a consumer population regarded by advertisers and content providers as one monolithic LGBTQ community. The series I examine-from The Slope, which premiered in 2010, to Strangers, released in 2017-voice their creators' and characters' marginalization from and even opposition to such an imagined community, through recourse to what I call a "bad queer" rhetorical practice, which uses ironic metacommentary to critique assimilationist values and tropes alongside queer identity policing. These series emerged, at least initially, as an alternative sphere of queer media production and a queer discursive mode that employs disidentification as a politicized strategy to challenge dominant LGBTQ scripts. Offering an irreverent alternative to mainstream and millennial LGBTQ cultural products, these "bad queer" web series express the plurality of the queer "community" and expose political contestations within its ranks, and in so doing serve as brand differentiation for a new generation of queer media producers.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Performing Resistance/Negotiating Sovereignty: Indigenous Women's Perofrmance Art in Canada - Taunton, Carla Jane (Queen's University, 2011)
Performing Resistance/ Negotiating Sovereignty: Indigenous Women’s Performance Art In Canada investigates the contemporary production of Indigenous performance and video art in Canada in terms of cultural continuance, survivance and resistance. Drawing on critical Indigenous methodology, which foregrounds the necessity of privileging multiple Indigenous systems of knowledge, it explores these themes through the lenses of storytelling, decolonization, activism, and agency. With specific reference to performances by Rebecca Belmore, Lori Blondeau, Cheryl L'Hirondelle, Skeena Reece and Dana Claxton, as well as others, it argues that Indigenous performance art should be understood in terms of i) its enduring relationship to activism and resistance ii) its ongoing use as a tool for interventions in colonially entrenched spaces, and iii) its longstanding role in maintaining self-determination and cultural sovereignty.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Embodying Sovereignty: Indigenous Women’s Performance Art in Canada - Taunton, Carla (Narratives Unfolding: National Art Histories in an Unfinished World, 2017)
Homi Bhabha’s pivotal 1994 book,The Location of Culture, begins with an epigraph from Heidegger’s “Building Dwelling Thinking”: “A boundary is not that at which something stops but, as the Greeks recognized, the boundary is that from whichsomething begins its presencing.” Cultural engagement, whether antagonistic or affiliative in nature, is produced performatively – not as a reflection of something that is given or set in stone, but as an ongoing process of negotiation.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Re-Inventing Art Practices: Indigenous Women Artists Building Community through Art and Activism in Rural and Remote Manitoba - Nagam, Julie (University of Manitoba, 2006)
his thesis documents and explores community-based and socially engaged art by Indigenous women artists. Their artwork is impacting and strengthening communities in Manitoba. The Thesis explores the use of dialogical aesthetics in performance and socially-engaged art by Indigenous women artists in rural and remote areas of Manitoba, and relates these aesthetics to the concept of activism through their art and relationship to their community. The aim of this research and this paper is to document, support and expose the work of a small pocket of Indigenous women artists in Manitoba who are acting as activists or social change agents based on their artwork. I have arrived at this conclusion first by their personal testimonies, second, by their art being socially conscious and lastly, by their art practices entrenched in the framework of dialogical aesthetics, community-based and site-specific ideologies.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

(Re)Mapping the Colonized Body: The Creative Interventions of Rebecca Belmore in the Cityscape. - Nagam, Julie (American Indian Culture and Research Journal, 2011)
The cityscape holds the memories of indigenous bones and bodies that resurrect a deep sense of place that exists in the landscape of the city of Toronto. This deep sense of place is part of a connection to the land and stories of place. In this article, the author bridges the creative work of Anishinaabe artist Rebecca Belmore with the living histories of the indigenous bodies and bones that are buried beneath the ground of the city of Toronto and the city of Vancouver. She argues that Belmore's artwork is part of the living archive that performs cultural memory and employs telling as part of an embodied experience and a political act. Belmore's performance work creates, records, and stores indigenous stories of place. This article uses the ideas of cultural theorists Katherine McKittrick, Mishuana Goeman, and Matthew Sparke. Each of these people brings a different element to theories of the body and space. This article also uses feminist geographers Alison Blunt and Gillian Rose's work in women's colonial geographies to unpack the affects of the map in colonial spaces and the colonial gaze. (Contains 4 figures and 50 notes.)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Becoming our future: global indigenous curatorial practice - Nagam, Julie; Tamati-Quennell, Megan; Lane, Carly (ARP Books, 2020)
"This book investigates international Indigenous methodologies in art curatorial practice from the geographic spaces of Canada, Aotearoa (New Zealand) and Australia. From a perspective of Indigenous peoples important place within society, this collection explores how Indigenous art and culture operate within and from a structural framework that is unique and is positioned outside of the non-Indigenous cultural milieu. Through a selection of contributions, Becoming Our Future articulates this perspective, defines Indigenous curatorial practice and celebrates Indigenous sovereignty within the three countries. It begins to explore the connections and historical moments that draw Indigenous curatorial practices together and the differences that set them apart. This knowledge is grounded in continuous international exchanges and draws on the breadth of work within the field. With contributions by Nigel Borell, Nici Cumpston, Freja Carmicheal, Karl Chitham, Franchesca Cubillo, Léuli Eshraghi, Reuben Friend, Jarita Greyeyes, Heather Igloliorte, Jaimie Isaac, Carly Lane, Michelle LaVallee, Cathy Mattes, Bruce McLean, Kimberley Moulton, Lisa Myers, Julie Nagam, Wanda Nanibush, Jolene Rickard, Megan Tamati-Quennell, and Daina Warren."-- Provided by publisher.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Knowledge Positions in Aotearoa and Turtle Island Art Museums - Eshraghi, Leuli; Ash-Milby, Kathleen; Nuku, Maia; Borell, Nigel (Artlink, 2020)
Art, performance, and spoken or now written text, all belong to the same register of cultural practice in the First Nations I am familiar with or belong to: ceremony. This ceremonial register takes place in a set of spaces created to enact cultural responsibilities to place, people and balance. Galleries and museums, as sites of cultural production and presentation, have the potential to nurture new ceremonies and new working methods.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Inuit Visual and Sensate Sovereignty in Alethea Arnaquq-Baril’s Angry Inuk - Burelle, Julie (Canadian Journal of Film Studies, 2020)
L’auteure soutient que le documentaire de 2016 d’Alethea Arnaquq-Baril, Angry Inuk (Inuk en colère), crée, grâce au cinéma, des espaces de « souveraineté visuelle » centrés sur l’« agentivité sensorielle » inuite (Raheja, 2010 ; Robinson, 2016). La réalisatrice propose un recadrage, selon un point de vue inuit, de la rhétorique dominante entourant la chasse aux phoques, pratique décriée violemment par des groupes de défense des droits des animaux. Plus qu’une simple réfutation de ces discours sudistes, ce film met de l’avant les connaissances inuites en lien avec le territoire et la gestion des ressources et remet en question les argumentaires libératoires soutenus par ces organismes, dont les raisonnements reconduisent des dynamiques coloniales plutôt que de les ébranler. Comme l’évoque son titre, le documentaire riposte à l’ire des protestataires anti-chasse aux phoques (dont la voix s’impose souvent au détriment des voix inuites, généralement tues), en créant un espace d’expression pour la colère inuite, présentée à la fois comme carburant et comme point de départ légitime et valide de la lutte contre les organismes en question. De façon centrale, le film met en scène des récits de chasse aux phoques s’appuyant sur une « agentivité sensorielle » inuite qui, aux yeux de Dylan Robinson, se manifeste sous la forme de « modes d’expression qui, à la fois, affirment une force culturelle et exercent une puissance affective auprès des personnes présentes ». Arnaquq-Baril propose ainsi des représentations de rires partagés, d’un froid ressenti, de sons joyeux de consommation communautaire de diverses parties du phoque, de même que des photos tirées de la campagne Twitter menée autour du mot-clic #sealfie ; cette campagne médiatique, ancrée dans une célébration humoristique et fière de la chasse inuite aux phoques, se veut en ce sens un contre-point au discours affectif simpliste et méprisant des organismes anti-chasse. En s’articulant autour de la résilience complexe propre aux Inuits, Inuk en colère incarne en soi une forme de souveraineté inuite, s’imposant au sein des récits qui participent à la sensibilisation du public quant aux enjeux entourant cette chasse. En outre, le film invite l’auditoire à réfléchir aux avenirs autochtones et à envisager de quelles manières l’activisme pour la défense des droits des animaux peut être décolonisé afin qu’il ne mène pas à la reconduction de dynamiques violentes d’extractivisme et de colonisation.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Dans toute son exubérance : Affirmation de soi et autoreprésentation chez Caroline Monnet - Marcoux, Gabrielle (Canadian Journal of Film Studies, 2020)
In this interview, multidisciplinary artist Caroline Monnet discusses how acts of critical self-representation open up new spaces for territorial, linguistic, and identity negotiations and affirmations for Indigenous creators. In this sense, Monnet expresses her desire to put forward exuberant, strong, and diverse representations of Indigenous women in order to counter pervasive rhetorical dynamics of victimhood conveyed by mass media and cinema. As she presents some of the visual and discursive techniques she develops through her films, installations, and photographic works, Monnet reflects on the constructive dialogues – as well as the moments of incommunicability – that emerge and fade within various spaces and contexts of creation and reception. She considers that her individual and collective creative projects fall within a pivotal period of self-determination for Indigenous artists; she thus provides a critical overview of current discourses of (re)concililation.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Les archives à l’épreuve du temps : les recadrements temporels des courts métrages de la série Souvenir - Huberman, Isabella (Canadian Journal of Film Studies, 2020)
This article examines how “colonial time” is called into question in two short films of the National Film Board of Canada’s series Souvenir, from 2015. The question of time lies at the heart of this series, for which the NFB commissioned contemporary Indigenous filmmakers to take up their archives of visual material on Indigenous peoples. The colonial temporal framework is at work in the vast archives of ethnographic and documentary film and photography on Indigenous peoples dating back to the early twentieth century, in which Indigenous people are often represented as part of “vanishing” cultures. Thus, in this article, I underscore the temporal interruptions that occur when ethnographic visual material of Indigenous peoples is put into the hands of contemporary Indigenous artists. I focus first on what it means to repurpose dehumanizing colonial archives and ask whether visual sovereignty is in fact possible within the archives. By analyzing the reappropriation of archival footage in the short films Mobilize by Caroline Monnet and Etlinisigu’niet (Bleed Down) by Jeff Barnaby, I elucidate how the filmmakers break with modes of colonial time through what I propose to call “reframings” that offer alternative ways of conceiving of time. By rehabilitating ethnographic images, these filmmakers refuse to project the material into the distant past and complicate the readability of Indigenous images in the archives, revealing how the reappropriation of old images can be just as powerful as the production of new ones.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le cinéma autochtone au Québec: de la représentation à la ré-appropriation - Bertrand, Karine (Contemporary French Civilization, 2019)
Cet article se penche sur les relations et collaborations récentes entre les cinéastes autochtones et québécois. Une brève exploration des représentations autochtones antérieures et du contexte contemporain de co-réalisation Québec/Autochtonie nous permet d’esquisser un portrait plus nuancé des nouvelles configurations transnationales du paysage cinématographique québécois. De même, les notions d’autochtonisation du médium, de souveraineté visuelle et de survivance nous aideront à mieux cerner les œuvres de fiction réalisées par des cinéastes autochtones, qui contribuent à l’enrichissement d’un cinéma qui propose de nouvelles façons d’habiter les territoires québécois/autochtones.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le collectif Arnait Video Productions et le cinéma engagé des femmes inuits: Guérison communautaire et mémoire culturelle - Bertrand, Karine (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)
Marie-Hélène Cousineau, qui regroupe des femmes inuits de la communauté d’Igloolik, utilise la vidéo pour démontrer l’importance de la femme inuit dans le développement et la cohésion de l’unité sociale et familiale de l’Arctique (passé, présent et futur). Soulignant la spécificité culturelle des femmes d’Igloolik, ainsi que la portée universelle de questions reliées par exemple à la maternité, au pouvoir et au potentiel des femmes qui sont considérées comme des agents de changement sociétal participant à la transmission et au renouvellement de la connaissance traditionnelle, les cinéastes d’Arnait ont participé à des projets novateurs (telle que l’initiative Live from the Toundra) où les outils technologiques (Internet, blogues, capsules vidéos, radio, satellite) ont servis à établir des ponts entre les di érentes communautés du Nord."
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L’œuvre documentaire d’Alanis Obomsawin et la voix des femmes autochtones. - Bertrand, Karine (De l'exclusion à la solidarité: regards intersectionnels sur les médias, 2020)
Résumé livre : "L’intersectionnalité, telle qu’élaborée par les féministes noires dans les années 1980, permet de réfléchir aux rapports de pouvoir dans leur complexe enchevêtrement. Au-delà d’un certain effet de mode, cette éthique est plus que jamais nécessaire pour comprendre le monde, à l’aube d’une décennie marquée par un virus ayant partout exacerbé la violence et les inégalités, et mis en évidence les systèmes de privilèges. Et qu’arrive-t-il lorsque l’on porte ce regard attentif sur les médias ? Les textes rassemblés dans cet ouvrage explorent avec aplomb les questions de l’inclusion et de l’exclusion médiatiques. Que décoder du traitement média réservé au port du hijab dans le sport, aux agressions sexuelles à l’endroit des femmes noires et autochtones, ou encore, de la place de la sourditude et des transidentités dans l’espace public? Un recueil qui amène son lot de réponses éclairantes et douloureuses, une rareté dans le paysage des études culturelles et médiatiques francophones."--Page 4 de la couverture
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Remembering Vancouver's Disappeared Women: Settler Colonialism and the Difficulty of Inheritance - Dean, Amber (University of Toronto Press, 2015)
"Between the late 1970s and the early 2000s, at least sixty-five women, many of them members of Indigenous communities, were found murdered or reported missing from Vancouver's Downtown Eastside. In a work driven by the urgency of this ongoing crisis, which extends across the country, Amber Dean offers a timely, critical analysis of the public representations, memorials, and activist strategies that brought the story of Vancouver's disappeared women to the attention of a wider public. Remembering Vancouver's Disappeared Women traces "what lives on" from the violent loss of so many women from the same neighborhood. Dean interrogates representations that aim to humanize the murdered or missing women, asking how these might inadvertently feed into the presumed dehumanization of sex work, Indigeneity, and living in the Downtown Eastside of Vancouver. Taking inspiration from Indigenous women's research, activism, and art, she challenges readers to reckon with our collective implication in the ongoing violence of settler colonialism and to accept responsibility for addressing its countless injustices
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Auto-histoires et représentations communautaires dans le cinéma des femmes autochtones - Bertrand, Karine (Canadian Journal of Film Studies, 2020)
In the last decade or so, cinema has revealed itself to be an ideal medium for the transfer and/or remediation of the spoken word as well as stories coming from oral tradition and Indigenous culture. Indeed, cinema is a place of expression which favours cyclical creativity and contributes to the decolonization of stereotyped images propagated by external voices that do not understand the subtleties of languages (real and symbolic) that are anchored in indigenous peoples’ cultural memory. By exploring indigenous cinema as practised by women of diverse nations, this piece demonstrates how cinema can induce the compression and dilation of time, to bring to the audience the fluidity of a story that has been reconfigured according to a new time and carried by spoken words that have chosen to either emancipate themselves from the image or to materialize themselves in it. Furthermore, this article illustrates how a new generation of Indigenous women use cinema to retrace and/or rewrite their personal narrative with the help of autobiographical or collective stories that travel back in time to fill in the blanks left by a fragile memory and to express their will to make peace with a difficult colonial past. Finally, the writings of Lee Maracle (I Am Woman, 1988) and Natasha Kanapé Fontaine (Manifeste Assi, 2014) are being brought forth to show how films such as Suckerfish (Lisa Jackson, 2004) Bithos (Elle-Máijá Tailfeathers, 2015) and Four Faces of the Moon (Amanda Strong, 2016) contribute to the individual and community healing of Indigenous peoples of Canada, through an aesthetic of reconciliation. The exploration of these works, therefore allows us to shed light on and better understand the roles/internal mechanisms of visual autobiographies in the larger context of reconciliation with individual and collective stories/memories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

From Great-Grandmothers to Great-Granddaughters: "Moving Life" in Baby Carriers and Birchbark Baskets - Kahsenni:io Nahwegahbow, Alexandra (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les porte-bébés et les paniers d'écorce autochtones sont, en tant que réceptacles, conçus pour porter et tenir. Outre cette fonction, ils sont aussi détenteurs d'histoires, de mémoire, et de liens familiaux. Créés individuellement et ornementés avec soin, ces objets constituent une sorte de portrait des femmes qui les ont produits, ainsi que des générations qui ont hérité des pratiques et des motifs servant à les fabriquer. En élargissant la définition de la notion de portrait de famille, cet article considère deux objets provenant de Bear Island, en Ontario. Le premier est un porte-bébé ayant appartenu à Madeline Katt Theriault, et le deuxième est un panier d'écorce vraisemblablement créé parson arrière-grand-mère Angele Katt. Par leur parenté, ces réceptacles englobent une histoire multigénérationnelle qui s'étend de l'arrière-grand-mère à son arrière-petite-fille
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Les arts wendats au service de la diplomatie et de la traite - de Stecher, Annette (Recherches amérindiennes au Québec, 2014)
Cet article porte sur les oeuvres artisanales des femmes wendates du xix ₑ siècle dans le contexte plus large des traditions des arts visuels wendats. En plus des objets commerciaux, l’auteure présente des objets faits pour être utilisés lors d’occasions cérémonielles et rituelles spéciales, et qui avaient aussi une valeur importante dans la communauté. Ces deux catégories d’artisanat dévoilent la façon dont les femmes wendates adaptaient leurs traditions artistiques aux sphères économiques et diplomatiques du monde colonial, et ce avec grand succès. Ces arts ont aidé la communauté à conserver une vision du monde amérindienne et ont préservé des traditions culturelles qui se sont perpétuées d’une génération à l’autre, tout en intégrant des innovations créatives. Ils démontrent aussi le rôle diplomatique important joué par les oeuvres présentées aux dignitaires eurocanadiens et européens dans un contexte cérémoniel, afin d’établir et de maintenir des relations politiques et économiques harmonieuses.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Art of Community - de Stecher, Annette (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
La nation huronne-wendat de Wendake (Lorette, Québec) a maintenu sa culture et son identité pendant des siècles, souvent en dépit de, et en résistance contre les pressions occasionnées par la présence missionnaire et les politiques coloniales. Cette survivance est tributaire de savoirs, de valeurs et de coutumes transmis de génération en génération. Cet article explore l'art de la communauté wendat et ses éléments constitutifs : la fabrication d'objets, la tradition orale, l'engagement actif des membres de la collectivité dans les pratiques traditionnelles, ainsi que l'adaptation des pratiques ancestrales aux préoccupations actuelles. Il montre comment la production artistique wendat, dans sa force expressive, contribue à la continuité et cohésion sociale de la nation wendat.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“Embodiment and Subjectivity”: Intersectional Black Feminist Curatorial Practices in Canada - Joachim, Joana (RACAR: revue d'art canadienne / Canadian Art Review, 2018)
Dans le contexte de l’héritage canadien de colonialisme et de profond racisme, les musées ont contribué à l’oppression des Noir.e.s, des communautés de couleur et des peuples autochtones en gardant le silence ou en supprimant certaines histoires sous prétexte d’« objectivité ». Cet article examine les pratiques commissariales de deux femmes noires canadiennes, Gaëtane Verna, directrice et conservatrice en chef de la galerie d’art contemporain The Power Plant, et Andrea Fatona, commissaire indépendante, afin de situer le commissariat critique à l’intérieur de perspectives afroféministes intersectionnelles. En conformité avec une base conceptuelle fondamentale de ce féminisme, je soutiens que ce qui rend l’acte commissarial « critique » est la reconnaissance non seulement de la position qu’une personne occupe dans la société, mais aussi de celles dont elle ne fait pas toujours l’expérience. En examinant les pratiques de ces deux femmes, je mets au jour une riche histoire de l’art et du commissariat des Noir.e.s au Canada.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Shelley Niro. Scotiabank Award. - Rice, Ryan; Nanibush, Wanda (Steidl Verlag, 2018)
Shelley Niro is widely known for her ability to explode myths, transgress boundaries and embody the ethos of her matriarchal culture in a wide variety of mediums including photography, installation, film and painting. Niro creates photographic series that emphasize the medium?s inherent capacity for narrative and representation. She pushes the limits of photography by incorporating Mohawk imagery, re-appropriating traditional stories such as Skywoman and The Peacemaker, and by focusing on contemporary subjects with wit, irony and campy humor. Niro marries portraiture, performance art and satire by having her subjects and herself perform for the camera in ways that gently invite audiences to rethink their beliefs and preconceptions about indigenous peoples and themselves. With compassion and deep insight, Niro opens up the fault lines and desires of gender, sexuality and culture to create images of freedom from the status quo in representation. Photography was a medium that helped subjugate indigenous peoples, but in Niro?s revolutionary hands it empowers
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Anthem: perspectives on home and native land - Rice, Ryan (Carleton University Art Gallery = Galerie d'art de l'Université Carleton, 2008)
Eight artists from across Canada create works identify varying forms of nationhood that either serve or detract from the concept of a national accord. Each artist explores the idea of ₃anthem₄ through a wide-angle lens, broadening the national discourse to include not only colonial histories, but also distinctive and multicultural liberties that take various forms: treaties, blood, languages, sexual orientation, faith, and oral traditions. The dynamic range of art works exhibited contribute to a more inclusive national narrative and expose and accept the diverse forms of nationalism that exist across the country.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Kwah í:ken tsi Iroquois - Rice, Ryan (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2008)
Catalogue d'exposition avec des textes de Ryan Rice, Françoise Charron, Emily Falvey et Hilda Nicholae.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Hochelaga revisité = Hochelaga revisited - Rice, Ryan (MAI (Montréal, arts interculturels), 2009)
Catalogue d'exposition avec des textes de Ryan Rice; Jason Baerg; Lori Blondeau; Martin Loft; Cathy Mattes; Nadia Myre; Ariel Lightningchild Smith.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Presence and Absence Redux: Indian Art in the 1990s - Rice, Ryan (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les années 1990 sont une décennie cruciale pour l'avancement et le positionnement de l'art et de l'autonomie autochtones dans les récits dominants des états ayant subi la colonisation. Cet article reprend l'exposé des faits de cette période avec des détails fort nécessaires. Pensé comme une historiographie, il propose d'explorer chronologiquement comment les conservateurs et les artistes autochtones, et leurs alliés, ont répondu et réagi à des moments clés des mesures coloniales et les interventions qu'ellesontsuscitéesdu point de vue politique, artistique, muséologique et du commissariat d'expositions. À la lumière du 150e anniversaire de la Confédération canadienne, et quinze ans après la présentation de la communication originale au colloque, Mondialisation et postcolonialisme: Définitions de la culture visuelle v, du Musée d'art contemporain de Montréal, il reste urgent de faire une analyse critique des préoccupations contemporaines plus vastes, relatives à la mise en contexte et à la réconciliation de l'histoire de l'art autochtone sous-représentée.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Déni et ignorance de l'historicité autochtone dans l'histoire de l'art occidentale - Uzel, Jean-Philippe (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Western art history long refused to recognize the historicity of Indigenous art, seeing it instead as a "primitive" mode of human expression. While the dynamism of Indigenous creation since the 1960s has made such an assertion impossible, the institutional recognition given contemporary Indigenous art in the art world is paradoxically accompanied by a lack of critical and theoretical analysis. Today, there is a genuine ignorance concerning Indigenous conceptions of history-their "regime of historicity"-on the part of Western art historians. This is all the more surprising given the recent "temporal turn" taken by the discipline, which emphasizes the question of mixed temporalities without acknowledging it as an essential dimension of Indigenous art. This paper revisits Western art history's long-standing denial of the historicity of Indigenous art, and then considers its current disregard for the ways Indigenous art allows different forms of temporality to coexist. The underlying thesis of the essay is that today's disinterest is, in fact, a prolongation of yesterday's denial.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Land and Beaded Identity: Shaping Art Histories of Indigenous Women of the Flatland - Robertson, Carmen (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Le territoire constitue une force déterminante dans la création artistique. Les prairies austères, notamment, exigent des artistes actuels comme de ceux qui les ont précédés une adaptation constante, déterminée par l'accès aux ressources et la nécessité de mobilité. Cet article s'intéresse à l'impact du territoire sur la pratique du perlage telle qu'exercée par les femmes autochtones. Il met en relation des exemples de perlage traditionnel conservés dans les collections muséales de la Saskatchewan avec les œuvres de trois artistes contemporaines autochtones des plaines, soit Ruth Cuthand, Judy Anderson et Katherine Boyer. La comparaison vise à mieux comprendre le processus intergénérationnel de transmission des pratiques ancestrales et ainsi révéler comment s'exprime le territoire dans les objets et œuvres ornés de perles, qui contribuent à façonner le récit des plaines.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Race-ing Art History: Critical Readings in Reace and Art History - Pinder, Kymberly N (Routledge, 2002)
This comprehensive anthology places issues of racial representation squarely on the canvas. Within these pages are representations of Nubians in ancient art, the great tradition of Westernmasters such as Manet and Picasso and contemporary work by lesser known artists.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Decolonial Pedagogy: Examining Sites of Resistance, Resurgence, and Renewal - Wane, Njoki Nathani; Todd, Kimberly L (Palgrave Macmillan, 2018)
"Through innovative and critical research, this anthology inquires and challenges issues of race and positionality, empirical sciences, colonial education models, and indigenous knowledges. Chapter authors from diverse backgrounds present empirical explorations that examine how decolonial work and Indigenous knowledges disrupt, problematize, challenge, and transform ongoing colonial oppression and colonial paradigm. This book utilizes provocative and critical research that takes up issues of race, the shortfalls of empirical sciences, colonial education models, and the need for a resurgence in Indigenous knowledges to usher in a new public sphere. This book is a testament of hope that places decolonization at the heart of our human community." -- Prové de l'editor.
Keywords: 1-Histoire de l'art; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art of the Northwest Coast - Jonaitis, Aldona.. (University of Washington Press, 2006)
"Art of the Northwest Coast is a comprehensive survey of the Native arts of the Pacific Northwest Coast, spanning the region from Puget Sound to Alaska, and proceeding from prehistoric times to the present. Incorporating the region's social history with the observations of anthropologists, historians of art, and Native peoples, this rich, vibrant book reveals how a complex web of factors informed these groups' varied responses to the changes and challenges brought about by contact with Europeans."-
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unpacking Culture: Art and Commodity in Colonial and Postcolonial Worlds - Phillips, Ruth B.; Steiner, Christopher Burghard (University of California Press, 1999)
Tourist art production is a global phenomenon and is increasingly recognized as an important and authentic expression of indigenous visual traditions. These thoughtful, engaging essays provide a comparative perspective on the history, character, and impact of tourist art in colonized societies in three areas of the world: Africa, Oceania, and North America. Ranging broadly historically and geographically, Unpacking Culture is the first collection to bring together substantial case studies on this topic from around the world.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Native Art of the Northwest Coast: A History of Changing Ideas - Townsend-Gault, Charlotte; Kramer, Jennifer (UBC Press, 2013)
This remarkable volume, many years in the making, records and scrutinizes definitions of Northwest Coast Native art and its boundaries. A work of critical historiography, it makes accessible for the first time in one place a broad selection of more than 250 years of writing on Northwest Coast "art." Organized thematically, its excerpted texts are from both published and unpublished sources, some not previously available in English. They cover such complex topics as the clash between oral and written knowledge, transcultural entanglement, the influence of surrealist thinking, and the long history of the deployment of Northwest Coast Native art for nationalist purposes. The selections are preceded by thought-provoking introductions that give historical context to the diverse intellectual traditions that have influenced, stimulated, and opposed each othe
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettling Native Art Histories on the Northwest Coast - Bunn-Marcuse, Kathryn B.; Jonaitis, Aldona (Native art of the Pacific Northwest : a Bill Holm Center series, 2020)
"This edited collection focuses on "unsettling" Northwest Coast art studies, bringing forward voices that uphold Indigenous priorities, engage with past and ongoing effects of settler colonialism, and advocate for practices for more accountable scholarship. Featuring authors with a variety of perspectives, backgrounds, and methodologies, Unsettling Art Histories offers new insights for the field of Northwest Coast art studies. Key themes include discussions of cultural heritage protections and long-standing defenses of natural resources and territory; re-centering women and the critical role they play in transmitting cultural knowledge across generations through materials, techniques, and creations; reflecting on the decolonization work being undertaken in museums; and examining how artworks function beyond previous scholarly framings as living documents carrying information critical to today's inquiries. Re-examining previous scholarship and questioning current institutional practices by prioritizing information gathered in Native communities, the essays in this volume exemplify various methods of "unsettling" and demonstrate how new methods of research have reshaped scholarship and museum practices."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Native Americans on Film: Conversations, Teaching, and Theory - Marubbio, M. Elise; Buffalohead, Eric L. (The University Press of Kentucky, 2012)
The film industry and mainstream popular culture are notorious for promoting stereotypical images of Native Americans: the noble and ignoble savage, the pronoun-challenged sidekick, the ruthless warrior, the female drudge, the princess, the sexualized maiden, the drunk, and others. Over the years, Indigenous filmmakers have both challenged these representations and moved past them, offering their own distinct forms of cinematic expression. Native Americans on Film draws inspiration from the Indigenous film movement, bringing filmmakers into an intertextual conversation with academic
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La loi sur les Indiens revisitée = The Indian Act revisited - Sioui-Durand, Guy; Picard-Sioui, Louis-Karl (Musée huron-wendat, 2009)
Catalogue d'exposition
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Femmes et violence de masse. - Myre, Nadia; Uzel, Jean-Philippe (Hors-série, 2018)
"Si tous les groupes humains sont touchés par la violence à grande échelle, les femmes la subissent sous des formes spécifiques, comme en témoignent les assassinats systémiques des femmes et des filles autochtones en Amérique du Nord et en Amérique latine, ou encore les nombreux conflits armés (Syrie, Lybie, Birmanie, entre autres) dans lesquels le viol est érigé en arme de guerre. Les deux phénomènes peuvent d'ailleurs se recouper puisque l'un des tout premiers féminicides à avoir été qualifié et documenté comme tel en Amérique est celui ayant été perpétré contre les femmes mayas durant la guerre civile guatémaltèque au début des années 1980. Cependant, les femmes ne sont pas seulement les victimes de la violence de masse, puisqu'elles sont aussi les premières à témoigner et dénoncer pour faire barrage à cette violence. Ce numéro hors-série regroupe des articles et des projets visuels qui décrivent et analysent la violence de masse liée au genre. Il s'agit de réfléchir sur la manière de représenter cette violence et d'en témoigner, d'autant plus qu'elle est bien souvent rendue invisible et inaudible par le patriarcat, le colonialisme, les intérêts politiques en présence ou l'impéritie de l'État."
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Walking With Our Sisters: une commémoration artistique pour le féminicide autochtone, en marche vers la décolonisation - Bruneau, Julie (Recherches féministes, 2017)
En réaction au féminicide autochtone au Canada et à l’inertie du gouvernement canadien, des groupes militants, des associations de familles et de proches des disparues ainsi que des groupes de femmes autochtones lancent régulièrement des actions commémoratives diverses. L’auteure a mené une enquête ethnographique lors de l’installation artistique commémorative Walking With Our Sisters présentée à Ottawa en 2015, projet réalisé par l’artiste métisse Christi Belcourt. Ainsi, l’auteure s’est interrogée sur la valorisation des femmes autochtones et leur prise de pouvoir au travers de ce processus. Elle remet en question la définition du féminisme occidental en prenant en considération les critiques formulées par les féministes autochtones
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Pratiques professionnelles en arts visuels issues de l'autochtonie et de la diversité à Montréal - Uzel, Jean-Philippe; Conseil des arts de Montréal (2017)
Rapport commandé par le Conseil des arts de Montréal
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

La réappropriation comme acte politique à l'ère de la décolonisation: l'oeuvre de Nadia Myre - Darsigny-Trépanier, Maude (Université du Québec à Montréal, 2019)
Ce mémoire cherche à dresser l'historiographie de l'artiste anishnabé Nadia Myre. Il s'agit d'une analyse à la fois qualitative et quantitative de près de 200 textes récoltés au sujet de l'artiste du début de sa carrière (1995) jusqu'en 2016. En plus d'offrir une visualisation de l'accomplissement de celle-ci avec la création d'une feuille de calcul, le présent mémoire cherche aussi à analyser les différents propos des auteur.es au sujet de la pratique d'une artiste autochtone en territoire appelé Canada. Les œuvres les plus marquantes de l'artiste sont également analysées en profondeur.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Ossements animaux dans l’art autochtone actuel Discours sur la mort, la résurgence et la guérison - Marcoux, Gabrielle (Recherches amérindiennes au Québec, 2015)
Les ossements animaux occupent des fonctions pratiques et rituelles extrêmement variées et complexes au sein des cultures ancestrales atikamekw et innue, que ce soit sur le plan spirituel, alimentaire, artistique ou autre. Encore aujourd’hui, en plus d’évoquer le trépas, les ossements font référence aux pratiques de communication avec les esprits animaux - comme la scapulomancie - et à la vision holistique du monde chez les peuples algonquiens. En intégrant des peaux et des fragments de squelettes animaux à leurs oeuvres portant sur des réalités contemporaines de pertes et de négociations intimes et collectives d’ordre culturel et territorial, les artistes Sonia Robertson et Eruoma Awashish parviennent à réactualiser le pouvoir de guérison et de résurgence traditionnellement associé aux ossements. Ainsi, la mise en scène d’os permet à ces créatrices de réécrire l’histoire de lieux chargés de sens et de réaffirmer l’importance actuelle de notions spirituelles, identitaires et culturelles autochtones ancestrales dans un contexte de réaffirmation collective et individuelle
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Reservation X - McMaster, Gerald R. (Goose Lane, 1998)
Catalogue d'une exposition tenue à l'origine au "First People's Hall of the Canadian Museum of Civilization", prise en charge par Gerald McMaster. Publié avec le "Canadian Museum of Civilization
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Afterlives of Indigenous archives: essays in honor of The Occom Circle - Schweitzer, Ivy; Henry, Gordon (Dartmouth College Press, 2019)
"Afterlives of Indigenous Archives offers a compelling critique of Western archives and their use in the development of “digital humanities.” The essays collected here present the work of an international and interdisciplinary group of indigenous scholars; researchers in the field of indigenous studies and early American studies; and librarians, curators, activists, and storytellers. The contributors examine various digital projects and outline their relevance to the lives and interests of tribal people and communities, along with the transformative power that access to online materials affords. The authors aim to empower native people to re-envision the Western archive as a site of community-based practices for cultural preservation, one that can offer indigenous perspectives and new technological applications for the imaginative reconstruction of the tribal past, the repatriation of the tribal memories, and a powerful vision for an indigenous future."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Futurisms: Transcending Past/Present/Future - Herr, Chelsea; Well-Off-Man, Manuela; Fricke, Suzanne Newman (IAIA Museum of Contemporary Indian Arts, 2020)
Indigenous Futurisms: Transcending Past/Present/Future investigates a major trend in Contemporary Native Art--the rise of futuristic or science-fiction inspired Native American art. The essays and artworks present the future from a Native perspective and illustrate the use of Indigenous cosmology and science as part of tribal oral history and ways of life. Several of the artists use sci-fi related themes to emphasize the importance of Futurism in Native cultures, to pass on tribal oral history and to revive their Native language. However, Indigenous Futurism also offer a way to heal from the traumas of the past and present--the post-apocalyptic narratives depicted in some of the artworks are often reality for Indigenous communities worldwide.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

You Want to Do What with Doda’s Stories? Building a Community for the Skins Workshops on Aboriginal Storytelling in Digital Media - Lewis, Jason E.; Fragnito, Skawennati (Community-Based Multiliteracies & Digital Media Projects : Questioning Assumptions and Exploring Realities, 2014)
Aboriginal Territories in Cyberspace (AbTeC) is a research network of artists, academics and technologists centrally concerned with Indigenous representation in, and production of, digital media (AbTeC, 2008). AbTeC investigates and identifies ways for Indigenous peoples to tell our stories via networked technologies, and in so doing, strengthen our communities while proactively participating in shaping cyberspace. We are based at Concordia University, in Montreal, Quebec.
Keywords: 1-Histoire de l'art; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Aesthetics, Violence, and Indigeneity. - Rickard, Jolene (Public, 2016)
This essay considers the intersectionality between the field of art history focused on the subject category of Native American or Indigenous art and Indigenous Studies. Methodological gaps in the field of art history are discussed through the canonical genre of landscape art with a comparative reference to key exhibitions; Land Spirit Power: First Nations at the National Gallery of Canada, (1992), The West As America: Reinterpreting Images of the Frontier, 1820-1920, (1991), Submuloc Show/Columbus Wohs (1992), Our Land/Ourselves: Contemporary Native American Landscape (1991) and Picturing the Americas: Landscape Painting from Tierra del Fuego to the Artic (2015). The aestheticization of the colonization of the Americas as represented in the genre of landscape art is interrogated as a form of historical violence that needs to be decolonized within the field of art history.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Partial Recall - Benally, Suzanne (New Press, 1992)
In Partial Recall, twelve Native American artists and writers look deep into the images that have shaped our ideas of "Indianness," and explore the complex relationship of photography to identity. For this volume, edited and introduced by Lucy Lippard, each contributor has chosen one or two photographs as the point of departure for their original poetic, historical, political, or autobiographical essays. With an additional portfolio of more than sixty photographs drawn from around the country, Partial Recall is a unique and valuable anthology.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Visualizing Sovereignty in the Time of Biometric Sensors - Rickard, Jolene (South Atlantic Quarterly, 2011)
Multiple expressions of sovereignty beyond a narrow legal interpretation are discussed through the artwork of contemporary Iroquois artists, G. Peter Jemison (Seneca), Alan Michelson (Mohawk), Samuel Thomas (Cayuga), and Marie Watt (Seneca). Michelson's installation at the Massena homeland security border checkpoint between the United States, Canada, and the Mohawk Nation, titled The Third Bank of the River, draws on the Guswentah or Two Row Wampum underscoring the problematic yet ongoing assertion of Haudenosaunee sovereignty. A link is made between the work of these artists and the 2008 Courtney Hunt film, Frozen River, based on the cultural and political understanding of the Two Row Wampum. The Guswentah is discussed as a demonstration of sovereignty and is historicized through Cayuga chief Deskaheh's call for the recognition of Haudenosaunee sovereignty at the League of Nations in Geneva, in 1923, John Mohawk's 1978 Basic Call to Consciousness, and more recently, Taiaiake Alfred's 1999 Peace, Power, Righteousness. These artists demonstrate the critical role they play in the ongoing formation of sovereignty as a visual or aesthetic issue in conjunction with its historic legal positioning.
Keywords: 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La muséologie collaborative au Canada : le positionnement du Musée McCord à l’égard des communautés autochtones - Franco, Marie-Charlotte (Musées, mutations…, 2019)
Résumé livre : 4e de couv.: Les mutations qui se sont amorcées à partir de la fin de la Seconde Guerre mondiale et qui connaissent une accélération rapide avec les crises sociales, culturelles, économiques et environnementales contemporaines ont transformé le paysage muséal et les visions dont les musées se soutiennent et qu'ils entretiennent. La plupart des travaux produits au cours de ces années ont été portés par ces transformations et y contribuent : la recherche en muséologie s'est elle-même dissociée de la recherche dans les musées dans les années 1980. De plus, quelque chose s'est noué entre un tournant communicationnel dans les musées et un développement de la réflexion théorique et critique sur la communication. Dans une approche résolument pluridisciplinaire, cet ouvrage se propose d'analyser ces évolutions dans leurs dimensions institutionnelles, culturelles, communicationnelles, historiques, patrimoniales. Les perspectives réunies ici contribueront, sans aucun doute, à mettre au jour les mouvements de fond actuels, les tendances qui travaillent les institutions elles-mêmes, et le poids de ces changements dans la formulation des enjeux théoriques en muséologie.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le musée: un outil de développement identitaire et communautaire en contexte autochtone? : le cas du Musée des Abénakis à Odanak - Franco, Marie-Charlotte (Université du Québec à Montréal, 2012)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La photographie comme affirmation. Aperçu d’un mouvement d’autoreprésentation - Guignard, Sophie (Inter, 2016)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Feature Film Production in Canada: A National and International Perspective - Goulet, Danis; Swanson, Kerry (ImagineNATIVE Film + Media Arts Festival, 2014)
The goal of this research is to examine Aboriginal feature film production in Canada, specifically within the genre of drama. This report documents the rise of Indigenous cinema worldwide and examines Canada's public funding landscape including funding allocations to Aboriginal feature film production from Canada's public funders of film over a five-year period from 2007 to 2012. This report also examines the barriers to feature film production for Aboriginal content creators in Canada, and suggests areas of opportunity that can be targeted in order to boost production in this sector. Aboriginal film production is a relatively young sector, with scarce research existing on the industry. To address this gap in the available information on the sector, the researchers expanded the scope of the study beyond public funding agencies in Canada to include data from public funding agencies in Australia and New Zealand. Aboriginal feature film production in Canada is situated within a global Indigenous cinema context. Australia and New Zealand, in particular, are two pillars of global Indigenous film that offer a realistic point from which to compare Canada's progress. As a result, data from Australia and New Zealand are included in the study, as well as one model in the United States.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art for a New Understanding: Native Voices, 1950s to Now - Hopkins, Candice; Well-Off-Man, Manuela; Besaw, Mindy N.; Crystal Bridges Museum of American Art (University of Arkansas Press, 2018)
"Art for a New Understanding, an exhibition from Crystal Bridges Museum of American Art that opened in October 2018, seeks to radically expand and reposition the narrative of American art since 1950 by charting a history of the development of contemporary Indigenous art from the United States and Canada, beginning when artists moved from more regionally-based conversations and practices to national and international contemporary art contexts. This accompanying book documents and expands on the histories and themes of this exciting exhibition. This fully illustrated volume includes essays by art historians and historians and reflections by the artists included in the collection. Also included are key contemporary writings--from the 1950s onward--by artists, scholars, and critics, investigating the themes of transculturalism and pan-Indian identity, traditional practices conducted in radically new ways, displacement, forced migration, shadow histories, the role of personal mythologies as a means to reimagine the future, and much more. As both a survey of the development of Indigenous art from the 1950s to the present and a consideration of Native artists within contemporary art more broadly, Art for a New Understanding expands the definition of American art and sets the tone for future considerations of the subject. It is an essential publication for any institution or individual with an interest in contemporary Native American art, and an invaluable resource in ongoing scholarly considerations of the American contemporary art landscape at large."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Trading Identities: The Souvenir in Native North American Art from the Northeast, 1700-1900 - Phillips, Ruth B. (Ruth Bliss) (McGill-Queen's University Press, 1998)
Indians in northeastern North America produced a variety of art objects for sale to travelers and tourists during the 18th and 19th centuries. This art is of high quality and great aesthetic interest, but has been largely ignored by scholars. This study combines fieldwork, art historical analysis
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Museum Pieces: Toward the Indigenization of Canadian Museums - Phillips, Ruth B. (Ruth Bliss) (McGill-Queen's/Beaverbrook Canadian Foundation studies in art history, 2011)
Ruth Phillips argues that these practices are "indigenous" not only because they originate in Aboriginal activism but because they draw on a distinctively Canadian preference for compromise and tolerance for ambiguity. Phillips dissects seminal exhibitions of Indigenous art to show how changes in display, curatorial voice, and authority stem from broad social, economic, and political forces outside the museum and moves beyond Canadian institutions and practices to discuss historically interrelated developments and exhibitions in the United States, Britain, Australia, and elsewhere. Drawing on forty years of experience as an art historian, curator, exhibition critic, and museum director, she emphasizes the complex and situated nature of the problems that face museums, introducing new perspectives on controversial exhibitions and moments of contestation. A manifesto that calls on us to re-imagine the museum as a place to embrace global interconnectedness, Museum Pieces emphasizes the transformative power of museum controversy and analyses shifting ideas about art, authenticity, and power in the modern museum.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Early Years of Native American Art History: The Politics of Scholarship and Collecting - Berlo, Janet Catherine (ACLS Humanities E-Book, 1992)
This collection of essays deals with the development of Native American art history as a discipline.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

In the Shadow of the Sun: Perspectives on Contemporary Native Art - McMaster, Gerald (Papers / Canadian Ethnology Service, 1993)
This volume makes available in English most of the essays written to accompany the Canadian Museum of Civilization's exhibition In the shadow of the sun. Not included from the original German publication are the exhibition catalogue section and the essays by Gisela Hoffmann, Bernadette Driscoll and Elizabeth McLuhan. However, Viviane Gray's article appears in this document for the first time. Complemented by images of contemporary Indian and Inuit art, the book provides an overview of the evolution of contemporary Canadian Native art. Regional styles as well as the styles of individual artists are discussed, and the various subjects, themes and techniques reflected in the works of art are examined
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

On Aboriginal Representation in the Gallery - Jessup, Lynda; Bagg, Shannon (Mercury series, 2002)
This book provides a glimpse of thirteenth-century life and death in a southern Ontario Iroquoian community. The renovation of a Toronto soccer field in 1997 resulted in the accidental discovery of an Iroquoian ossuary--a large pit containing the remains of at least 87 people. The pit was excavated and recorded, and the remains reburied in accordance with the wishes of the Six Nations Council of Oshweken. Scientific analyses of the bones resulted in a remarkably detailed demographic profile of the Moatfield people, along with indicators of their health and diet. The book reports these findings and includes a complete database of maps and profiles on an accompanying CD-ROM. Ronald F. Williamson is president of Archaeological Services Inc., Toronto. Susan Pfeiffer is professor of anthropology at the University of Toronto. Source: Publisher
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

D’Indigena à Sakahàn. Éléments de réflexion pour une affirmation autochtone dans l’art contemporain - Franco, Marie-Charlotte (Inter, 2016)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Àbadakone: feu continuel = continuous fire - Dickenson, Rachelle; Hill, Greg A.; Lalonde, Christine (Musée des beaux-arts du Canada, 2020)
Ce survol de l'art contemporain indigène, qui connut un succès retentissant dès son ouverture en novembre 2019, a été prolongé jusqu'au 4 octobre au Musée des beaux-arts du Canada. Àbadakone permet de découvrir des œuvres de plus de 70 artistes qui revendiquent leur appartenance à quelque 40 nations, ethnies et tribus de 16 pays, dont le Canada. Traitant des thèmes de la continuité, de l'activation et de l'interdépendance, Àbadakone explore la créativité, les préoccupations et la vitalité qui marquent l'art indigène de presque tous les continents. L'exposition est organisée par les conservateurs du Musée des beaux-arts du Canada Greg A. Hill, Christine Lalonde et Rachelle Dickenson, conseillés par les commissaires Candice Hopkins, Ariel Smith et Carla Taunton, ainsi que par une équipe d'experts du monde entier. .
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Amérique du Nord: arts premiers - Berlo, Janet Catherine; Phillips, Ruth B. (Terre indienne, 2006)
Replaçant chaque oeuvre dans son contexte familial, social, géographique, économique et spirituel, cet album présente l'art des peuples premiers d'Amérique du Nord, des Inuits aux peuples des déserts du sud-ouest des Etats-Unis, des origines à la période contemporaine
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Beat Nation: Art, Hip Hop and Aboriginal Culture - Ritter, Kathleen; Willard, Tania (Vancouver Art Gallery, 2012)
Catalgoue d'exposition
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Regards d'acier: portraits par des artistes autochtones. - Kunard, Andrea; Loft, Steve (Musée des beaux-arts du Canada, 2011)
Catalogue d'exposition avec plusieurs textes.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Manifest Manners: Narratives on Postindian Survivance - Vizenor, Gerald Robert (Univ. of Nebraska Press, 2010)
Combines post-modern theory with the comic wisdom of the tribal trickster to explore the effects of nostalgic simulations of "Indian-ness".
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigena: Perspectives Autochtones Contemporaines - Martin, Lee-Ann; McMaster, Gerald (Musée canadien des civilisations, 1992)
Catlogue d'exposition avec plusieurs textes.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L’appropriation culturelle et les peuples autochtones: entre protection du patrimoine et liberté de création. - Nepton-Hotte, Caroline; Jérôme, Laurent; Uzel, Jean-Philippe; Darsigny-Trépanier, Maude (GRIAAC, Groupe de recherche interdisciplinaire sur les affirmations autochtones contemporaines, 2019)
Le colloque « L’appropriation culturelle et les peuples autochtones : entre protection du patrimoine et liberté de création », organisé à l’UQAM en avril 2018, a suscité un dialogue fructueux à propos des multiples dimensions de l’appropriation culturelle. Réunissant des acteurs des milieux des arts et de la culture, du droit, de la politique, du tourisme et de la santé, ce colloque a permis de susciter des avenues de réflexion ainsi que différentes pistes d’action. Ce colloque, organisé par le Groupe de recherche interuniversitaire sur les affirmations autochtones contemporaines (GRIAAC-UQAM) en collaboration avec la Faculté des sciences humaines (FSH), la Société Recherches amérindiennes au Québec (SRAQ) et l’organisme Terres en vues, visait à réunir des experts et des praticiens des cultures et des sociétés autochtones (Premières Nations, Inuits et Métis), mais aussi des spécialistes des questions juridiques liées à la propriété intellectuelle, au droit d’auteur et aux droits collectifs, autour d’une question commune : comment respecter et protéger les traditions, les conceptions, les symboles, les savoirs, les patrimoines culturels matériels et immatériels autochtones, tout en continuant à favoriser la créativité et les échanges entre les cultures? À travers des présentations générales et des tables rondes réalisées sous forme d’ateliers, ce colloque visait non seulement à poser les termes de ces questions complexes, mais également à identifier des pistes concrètes d’actions pour que soient reconnues et respectées l’histoire, les lois et l’épanouissement tant des cultures autochtones que des autres cultures, et en particulier de la culture québécoise.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Présences, mémoires individuelles et plurielles comme dispositifs de construction dans le travail des créatrices autochtones - Pageot, Édith-Anne (Espace, 2018)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Decolonize Me - Igloliorte, Heather; Loft, Steve; Croft, Brenda L. (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2012)
Catalogue d'exposition avec des textes de Loft, Igloliorte et Croft. Galerie d'art d'Ottawa.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

SakKijâjuk: Art and Craft from Nunatsiavut - Igloliorte, Heather; Broomfield, Jenna Joyce; Chaulk, Aimee; Lalonde, Christine; Pottle, Barry (Goose Lane Editions, 2017)
Nunatsiavut, the Inuit region of Canada that achieved self-government in 2005, produces art that is distinct within the world of Canadian and circumpolar Inuit art. The world's most southerly population of Inuit, the coastal people of Nunatsiavut have always lived both above and below the tree line, and Inuit artists and craftspeople from "Nunatsiavut have had access to a diverse range of Arctic and Subarctic flora and fauna, from which they have produced a stunningly diverse range of work. Artists from the territory have traditionally used stone and woods for carving; fur, hide, and sealskin for wearable art; and saltwater seagrass for basketry, as well as wool, metal, cloth, beads, and paper. In recent decades, they have produced work in a variety of contemporary art media, including painting, drawing, printmaking, photography, video, and ceramics, while also working with traditional materials in new and unexpected ways. SakKijâjuk: Art and Craft from Nunatsiavut is the first major publication on the art of the Labrador Inuit. Designed to accompany a major touring exhibition organized by The Rooms Provincial Art Gallery of St. John's, the book will feature more than 80 reproductions of work by 45 different artists, profiles of the featured artists, and a major essay on the art of Nunatsiavut by Heather Igloliorte. SakKijâjuk - "to be visible" in the Nunatsiavut dialect of Inuktitut - provides an opportunity for readers, collectors, art historians, and art aficionados from the South and the North will come into intimate contact with the distinctive, innovative, and always breathtaking work of the contemporary Inuit artists and craftspeople of Nunatsiavut
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

D'horizons et d'estuaires: entre mémoires et créations autochtones - Larivée, Camille; Eshrāghi, Léuli (Éditions Somme toute, 2020)
"D'horizons et d'estuaires. Entre mémoires et créations autochtones est une collection d'essais réunissant les voix de 16 artistes, commissaires, historien·ne·s de l'art et travailleur·se·s culturel·le·s autochtones, tant francophones qu'anglophones, œuvrant dans les territoires que l'on nomme Québec. Faisant suite à des expositions, des performances, des résidences d'artistes et des discussions mises en place lors du Projet Tiohtià:ke (2017-2019) du Collectif des commissaires autochtones, ces textes honorent les relations et les affinités qui sont au cœur de ces pratiques en arts visuels. Quelle place occupe actuellement les créations visuelles autochtones dans la société québécoise? Comment les créateur·trice·s imaginent-iels le futur de leurs expressions culturelles? Par la diversité des points de vue et les enjeux soulevés par ces écrits, ce livre pose des questions cruciales sur l'avenir des arts autochtones et ouvre la porte à des dialogues longtemps attendus au Québec qui, nous l'espérons, permettront de créer de réels changements positifs. Il est maintenant temps de plonger dans ces imaginaires collectifs éblouissants et de nager dans les eaux ondulantes de ces mémoires résilientes. Le texte est accompagné de 28 photographies d'œuvres d'artistes autochtones."-- Fourni par l'éditeur
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Remix New Modernities in a Post-Indian World - Baker, Joe; McMaster, Gerald (Heard Museum/Natural Museum of American Indian, 2007)
Published in conjunction with the exhibition of the same name, on view at the Heard Museum in Phoenix, Arizona, from October 6, 2007, to April 27, 2008, and at the George Gustav Heye Center, National Museum of the American Indian, in New York, New York, from May 26 through September 30, 2008
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La voix du territoire: représentations territoriales plurielles dans l'œuvre d'Eruoma Awashish - Ruestchmann, Clara (Université de Montréal, 2019)
Le territoire (Nitaskinan), dans la pensée autochtone, est une notion centrale et pluridimensionnelle ; elle induit un territoire historique, géographique et politique revendiqué ainsi qu'un territoire cosmologique inscrit au cœur de rites et de croyances ancestrales. C'est l'articulation et l'harmonisation de ce territoire pluriforme que l'artiste atikamekw Eruoma Awahish entreprend de présenter dans son œuvre. Ce mémoire adresse la manière dont l'artiste représente le territoire, à la fois dans une volonté d'ancrage traditionnel et de réactualisation contemporaine dans une perspective diachronique. L'artiste déploie une esthétique franche et colorée, elle s'emploie à renverser les codes du colonialisme et développe des stratégies afin de contribuer aux revendications et à l'affirmation territoriale des Premières Nations. Par le biais d'une production artistique politisée, Eruoma Awashish applique un prisme décolonisateur ; elle réinvestit une histoire coloniale et offre aux symboles et aux narrations autochtones une place centrale et active. Ce mémoire met subséquemment l'emphase sur la capacité des nations autochtones à s'adapter, à s'auto-définir et à s'auto-représenter. Les artistes se font les témoins et les vecteurs d'une affirmation et d'une recherche de souveraineté qui, chez Awashish, est à la fois visuelle, culturelle et territoriale. Déployant une approche interdisciplinaire, à l'image de la production de l'artiste, ce mémoire prend pour appui les écrits de penseur.se.s autochtones afin de présenter la démarche et la production d'une artiste ancrée dans un contexte contemporain complexe soumis à de nombreuses revendications politiques, culturelles et territoriales. Si les œuvres d'Awashish transmettent et diffusent ces revendications, elles sont toutefois, avant tout, le reflet de croyances et d'une histoire territoriale atikamekw.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le jardin en ville, le cas des Jardins éphémères à Québec. Stratégie marchande et critique postcoloniale - Pageot, Édith-Anne (Globe, 2012)
Cet article se penche sur la portée philosophique du projet intitulé Jardins éphémères, un ensemble de onze jardins temporaires réalisés dans le cadre des activités visant à célébrer le 400ₑ anniversaire de la fondation de la ville de Québec au cours de l’été 2008. L’organisation, les intentions et les principaux thèmes sous-jacents aux différents projets sont présentés dans leur ensemble. Le jardin intitulé « Wampum 400 », créé par deux artistes autochtones, Domingo Cisneros et Sonia Robertson Piekuakamilnu, fait l’objet d’un commentaire plus long. L’analyse montre que le projet Jardins éphémères dans son ensemble incarnait les principaux enjeux actuels du jardin en ville. Certains aspects reconduisaient la vision idéelle du jardin, d’autres satisfaisaient la logique touristique de l’événement et d’autres, enfin, développaient une position critique qui concerne la réappropriation d’un espace à usage collectif et, du coup, interrogeaient les fondements épistémologiques et ontologiques du « jardin ».
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L'art dans tous ses territoires au jardin des Premières-Nations: regards sur l'immatériel dans les œuvres du Concours d'œuvre murale éphémère - Lauzon Chiasson, Gabrielle (Université de Montréal, 2019)
De 2003 à 2017, le jardin des Premières-Nations du Jardin botanique de Montréal a été le lieu d'exposition de 12 œuvres d'artistes autochtones dans le cadre du Concours d'œuvre murale éphémère lancé par Sylvie Paré. Ce mémoire rassemble l'ensemble de cette exposition afin d'en relever le discours général et les liens que les œuvres entretiennent entre elles, avec le Jardin et avec les territoires
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La crise d'Oka en récits: territoire, cinéma et littérature - St-Amand, Isabelle (Collection InterCulture, 2015)
La crise d'Oka marque un véritable moment de rupture dans lesrelatlons entre les premiers peuples et les colonies de peuplement. Dans les suites immédiates de l’échec de l’accord du lac Meech, ce long siège armé de 78 jours rend visible une présence autochtone que les sociétés québécoise et canadienne avaient imaginée évanouie. Àl’inverse, l’opposition à l’empiétement mis en œuvre à Kanehsatàke età Kahnawàke réactive une longue histolre de résistance au projet colonial d'appropriation des terres et d'effacement des peuples autochtones. Ce livre envisage la crise d'Oka, ou la résistance à Kanehsatàke, comme un espace de focalisatlon où se donne à voir larelation globale entre les peuples. Qu'est-ce que l'événement fait surgir, transforme et crée, dans la scénographie du siège, mais aussi dans les films documentaires et les récits littéraires, autochtones et allochtones? À l'heure où une nouvelle génération revient sur cette crise politique aux enjeux non résolus, ce livre ouvre un espace où entrent en relation et s'affrontent différents intérêts, connaissances et expressions relatifs à ce conflit territorial. Il engage une réflexion épistémologique essentielle à un processus de décolonisation aussi impératif qu'exigeant.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Nadia Myre, en[counter]s - Tougas, Colette; Couëlle, Marcia; Myre, Nadia (Éditions Art mûr, 2011)
Nadia Myre is a multidisciplinary artist whose work explores themes of language, culture, and memory, and who sources the culture of her Algonquin ancestors as a way of confronting contemporary realities. This monograph provides a comprehensive first look at this Montreal-based artist's remarkable career
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Encounters on Contested Lands: Indigenous Performances of Sovereignty and Nationhood in Québec - Burelle, Julie (Performance works, 2019)
Encounters on Contested Lands analyzes films, plays, visual art, and protest marches by Indigenous artists in Québec, Canada, to explore the performance of cultural identity, sovereignty, and nationhood in Québec's independence movement
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Entre-deux mondes: métissage, identité et histoire sur les traces de Sonia Robertson, Sylvie Paré et Rebecca Belmore, ou, Les parcours artistiques de trois femmes artistes autochtones, entre la mémoire et l'audace - Charce, Chloë (Université du Québec à Montréal, 2008)
Ce mémoire est globalement axé sur la légitimité de la notion d'identité dans les contextes postcolonial et postmoderne. Plus précisément, il porte sur le concept de métissage dans l'art actuel à l'heure de la mondialisation culturelle, lieu propice à un renouvellement de l'identité et de l'imaginaire pour les communautés des Premières Nations d'Amérique du Nord. Il est divisé en deux parties. Les deux premiers chapitres énoncent une perspective socio-ethnohistorique autour des notions d'identité et de métissage, alors que le troisième chapitre expose un point de vue analytique à partir d'un corpus d'oeuvres de trois femmes artistes autochtones du Québec et de l'Ontario s'exécutant sur la scène artistique contemporaine, soit Sonia Robertson, Sylvie Paré et Rebecca Belmore. Plus spécifiquement, le premier chapitre fait état des connaissances et des discours sur les définitions même d'identité et de métissage dans les contextes colonial / postcolonial et moderne / postmoderne. Par extension, je pose cette question concernant l'hybridité culturelle: s'agit-il d'un principe d'homogénéisation et d'essentialisation des cultures ou d'un facteur garant d'hétérogénéité, favorable au mélange et aux échanges interculturels ? Le deuxième chapitre, quant à lui, énonce les contextes de dépossession territoriale et d'exiguïté culturelle dans lesquels ont été contraints les peuples des Premières Nations depuis l'époque coloniale. Il fait aussi mention des métissages artistiques (post)postmodernes, qui contribuent à un renouveau de l'imaginaire amérindien. Dans un esprit à la fois de contestation face à l'image folklorisée de l'« Indien » et de transmission des valeurs traditionnelles, les artistes autochtones font place à la réappropriation culturelle. Enfin, le troisième chapitre souligne les parcours identitaires de Sonia Robertson (Ilnue), Sylvie Paré (métisse huronne-wendat) et Rebecca Belmore (Anishinabekwe). À titre de comparaison, j'analyse un corpus d'installations et de performances sous le thème de la mémoire et de l'identité en lien avec les concepts élaborés dans les chapitres précédents. Le choix d'examiner le travail de trois femmes artistes provenant de communautés différentes permet de rendre compte de réflexions personnelles de la part de femmes autochtones face à la culture dominante et par rapport à leur culture d'origine. Ce choix vise par ailleurs à circonscrire, au sein même de leur production, l'importance de la tradition en fonction de leur affirmation identitaire. Je souhaite ainsi étudier comment ces propositions se positionnent dans un contexte de déterritorialisation culturelle en fonction d'une réalité post(néo)colonialiste, corrélative d'un entre-deux mondes. Pour conclure, je reviens sur les questions d'identité, de mémoire et de territoire en soulignant l'importance idéologique du combat identitaire des communautés autochtones, qui vise la mise en échec des préjugés et des constructions mythiques persistantes entre le « Blanc » et l' « Indien ». Je mesure en ce sens l'impact que pourrait avoir la pensée universelle amérindienne sur nos sociétés hypermodernes en crise et en quête de valeurs.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Jeff Thomas. Droits de cité - Sabet, Aseman (Espace, 2014)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Monuments, Movements, and the Photography of Jeff Thomas. Discussion between Mikinaak Migwans (Curator of Indigenous Art, Art Museaum) and Maria Hupfield, with Syrus Marcus Ware - Thomas, Jeff
Interview vidéo et écrite.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Repenser le temps et l'espace, du wampum au selfie - Vigneault, Louise (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
This article considers the way certain Indigenous artists are reviving conceptions of territory and history that are anchored in secular epistemologies and the construction of knowledge. Such conceptions provide a way for these artists to respond to colonial appropriation, reactivate interrupted dialogues, engender new forms of territorialization, and create places of commemoration and memory preservation. Similar to the historiographical deconstruction performed by thinkers and activists such as Vine Deloria Jr. and Taiaiake Alfred, these artists’ works offer a model of autonomy and environmental balance. While some are reviving mnemonic practices, such as the making of wampum, which traditionally preserve memories of alliances and conflicts, others have embraced Internet and selfie technologies as a means of creating new spaces for speech and recognition
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Mises en récit 2.0 de l'activisme autochtone. The Indigenous Archival Photo Project et What Brings Us Here - Pinto Ferretti, Alexia (L'agir en condition hyperconnectée. Art et images à l'oeuvre., 2020)
La question de la mémoire en condition hyperconnectée s’articule également dans le potentiel des réseaux sociaux pour la mise en visibilité de différents mouvements activistes autochtones au Canada. À travers deux études de cas, le projet The Indigenous Archival Photo Project par l’écrivain Paul Seesequasis (Cri des plaines) et la page Instagram What Brings Us Here mettant en vedette les groupes d’activistes à Winnipeg The Bear Clan et Drag the Red, ce chapitre réfléchit à la manière dont les créateur.rice.s autochtones utilisent les réseaux sociaux comme des vecteurs d’agentivité narrative témoignant de différents enjeux touchant les communautés. Ces projets doivent être considérés comme des opérateurs de changements, car ils participent à la valorisation des voix autochtones et à l’instauration de divers réseaux de solidarité. Par différentes stratégies conversationnelles en ligne, ces projets renouent ainsi avec le communautarisme propre aux médiums de communication traditionnels autochtones où le dialogue est primordial.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Aestetics: Native Art, Media and Identity - Leuthold, Steven M.... (University of Texas Press, 1998)
What happens when a Native or indigenous person turns a video camera on his or her own culture? Are the resulting images different from what a Westernized filmmaker would create, and, if so, in what ways? This book discusses the core concepts of aesthetics and indigenous culture and examines the work of American Indian documentary filmmakers
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Numéro spécial : Cinémas et médias autochtones dans les Amériques : récits, communautés et souverainetés - Dudemaine, André; Marcoux, Gabrielle; St-Amand, Isabelle (Canadian Journal of Film Studies, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Queering Decolonization – Two Spirit Resistance Across Borders From Turtle Island to Palestine (2019)
Avec Alex Wilson, Jeffrey McNeil, Teddy Syrette, May Ela and Ahmed Maswadeh.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas--from Nunavut to Tierra del Fuego. Through three themes--landscape, territory, and trade--this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."--Résumé de l'éditeur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Transformations and Remembrances in the Digital Game We Sing for Healing - LaPensee, Elizabeth A. (Transmotion, 2017)
Digital games, with their capacity for expression and facilitating experience through code, design, art, and audio, offer spaces for Indigenous creatives to contribute to Gerald Vizenor’s characterization of survivance as an active sense of Native presence. Indigenous digital games can be acts of survivance both in the ways they are created as well as the resulting designs. We Sing for Healing is an experiment in developing an Indigenous digital game during limited Internet access that resulted in a musical choose-your-own adventure text game with design, art, and code by Anishinaabe, Métis, and Irish game developer Elizabeth LaPensée alongside music by Peguis First Nation mix artist Exquisite Ghost. The non-linear gameplay expresses traditional storytelling patterns while enabling players to poetically travel in, through, and around traditional teachings. The design uses listening, choosing, and revisiting to reinforce what is best described as a non-linear loopular journey.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Honour water: Gameplay as a Pathway to Anishinaabeg Water Teachings - LaPensée, Elizabeth (Decolonization: Indigeneity, Education & Society, 2018)
Digital games can uniquely express Indigenous teachings by merging design, code, art, and sound. Inspired by Anishinaabe grandmothers leading ceremonial walks known as Nibi Walks, Honour Water (http://www.honourwater.com/) is a singing game that aims to bring awareness to threats to the waters and offer pathways to healing through song. The game was developed with game company Pinnguaq and welcomes people from all over to sing with good intentions for the waters. The hope is to pass on songs through gameplay that encourages comfort with singing and learning Anishinaabemowin. Songs were gifted by Sharon M. Day and the Oshkii Giizhik Singers. Sharon M. Day, who is Bois Forte Band of Ojibwe and one of the founders of the Indigenous Peoples Task Force, has been a leading voice using singing to revitalize the waters. The Oshkii Giizhik Singers, a community of Anishinaabekwe who gather at Fond du Lac reservation, contribute to the healing for singers, communities, and the waters. Water teachings are infused in art and writing by Anishinaabe and Métis game designer, artist, and writer Elizabeth LaPensée. From development to distribution, Honour Water draws on Indigenous ways of knowing to reinforce Anishinaabeg teachings with hope for healing the water.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

SPEAR: a Framework for Indigenous Cultural Games - LaPensee, Elizabeth (ANTARES: Letras e Humanidades, 2020)
Video games, which uniquely interweave design, code, art, and sound, can be an especially robust way to express Indigenous cultures. Such games should involve Indigenous people in meaningful roles throughout design and development from conceptualization to distribution with a focus on building capacity to encourage self-determination for Indigenous game developers. This call to action informs SPEAR (Sovereignty, Positionality, Equity, Advocacy, and Reciprocity), a framework for design and development informed by the Indigenous cultural game Thunderbird Strike.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Recherche-création; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“I see my ancestors”: Exploring Tribal College Student Experiences Playing When Rivers Were Trails - Emmons, Nichlas; LaPensee, Elizabeth (AlterNative: An International Journal of Indigenous Peoples, 2021)
The educational video game, When Rivers Were Trails, was launched in 2019. The purpose of the game is to teach players about Indigenous perspectives of history, US federal allotment policies affecting tribal nations, and some of the effects of these policies on Indigenous peoples. This article explores tribal college student experiences playing When Rivers Were Trails in hopes that it provides the basis for further research into how tribal college faculty may be able to teach the game within their own classrooms. Tribal colleges and universities were created by tribal nations to provide for the higher education needs of their citizens. Using phenomenological research methods, seven college students volunteered to participate in a brief study about their experiences playing the video game. Upon transcription and analysis of the interview data, three themes were developed that capture how these students define their experience with When Rivers Were Trails: feelings of representation, histories of land dispossession, and resilience of communities.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

“We All Stand Side by Side”: An Interview with Elizabeth LaPensée - Hearne, Joanna (Studies in American Indian Literatures, 2017)
Keywords: 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Histoire de l'art

Imagining Indigenous Digital Futures: An Afterword - Raheja, Michelle (Studies in American Indian Literatures, 2017)
In lieu of an abstract, here is a brief excerpt of the content: As I sit writing in my kitchen while the forces of the U.S. military state are brought to bear on thousands of Standing Rock water stewards and land protectors and their allies in Cannonball, North Dakota, I consider how this sail special issue on digital Indigenous studies not only represents a collection of essays about the critical work Indigenous women are performing in their various digital projects but also illustrates that these online “Indigenous territories” (Hearne), crafted on social media platforms such as Twitter and Facebook, save lives. Every single day since the protectors first gathered to oppose the proposed 1,170-mile Dakota Access pipeline (a project that would potentially contaminate the Missouri watershed and the Ogallala Aquifer and desecrate Dakota sacred sites), digital independent and social media have constantly covered the story. At least 1.3 million Facebook users checked in virtually at Oceti Sakowin and other Indigenous camps and communities to ensure that support presence is recognized, while the world monitors the presence of the military and police force gathering at the construction site to curb further violence. The Standing Rock gathering offers hope to networked Indigenous youth, a demographic between three and ten times as likely to commit suicide than the national average peer rate. The Nodapl action in the Indigenous imaginary is an invitation to stand at the front lines of a global movement to protect water and land resources for all living beings on this planet and to draw attention to and support those whose lives and ways of being are in peril through overt military action and consequential environmental destruction. It is also an occasion, in the words of Jolene Rickard, “to invest in the apparatus of the imagination” (Bernardin). One need only look at the online art, handwritten signs, and logos representing #nodapl, #standingrock, [End Page 172] #waterislife, and #rezpectourwater to see the ways in which Indigenous artists are creatively and powerfully envisioning this movement, most often immersed with work that features strong images of Native women and girls, the community backbone and life force. Or we need only view digital videos like computer animator and artist Joseph Erb’s black-and-red graphic history of Standing Rock, “Mni Wiconi / Water Is Life” (https://www.youtube.com/watch?v=kXoy5lzpjiM), and first-person game platforms like Elizabeth LaPensée’s Thunderbird Strike, which extend the conversations at Standing Rock to the struggles over Enbridge’s Alberta tar sands pipeline and fracking practices as players work to undo and prevent further environmental degradation. Following Idle No More’s digital and geospatial (re)articulation of Indigenous territories, we are now living and loving and hoping in this historic moment as new ways of relating to one another and living in deep connection with the land and all its forms of life are being physiologically, intellectually, and spiritually forged at the geospatial confluence of the Missouri and Cannonball Rivers. They are being forged as well through the confluences of digital rivers on our electronic devices and in our online conversations about the beauty and devastation of the events that are unfolding in Standing Rock. Susan Bernardin’s essay in this issue on Heid E. Erdrich’s “Pre-Occupied” considers the meaning of rivers to Native peoples and contends that images of waterways, particularly the Mississippi, are mobilized “to make visible the continuing claims of this and other imperiled riverine systems.” In her introduction, Joanna Hearne asks us, “How might such an intersection of digital and Indigenous specificities take place in a way that is ‘native to the device’; that is, how might Indigenous specificity be embedded in shared platforms that are therefore central to all of our digital lives?” The essays in this special issue respond to this question by theorizing digital media in fresh and innovative ways. Many of us teach digital humanities courses or classes with strong digital media content, but we lack the language for critically engaging this new field on its own terms as it intersects, extends, and radically reconceptualizes more familiar research areas such as cinema studies, Indigenous / Native American studies, communication, literature, art, and history.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Thunderbird Strike: Survivance in/of an Indie Indigenous Game - LaPensée, Elizabeth (Video Game Art Reader 2.1, 2018)
Thunderbird Strike, a 2D side-scroller developed by Elizabeth LaPensée, allows a player fly from the Tar Sands to the Great Lakes as a thunderbird protecting Turtle Island with searing lightning against the snake that threatens to swallow the lands and waters whole. The game encouraged players to learn about the indigenous culture, reflect on water protection and alternative energy sources, and gain awareness of risks posed by oil pipeline construction for the conveyance of tar sands.Thunderbird Strike was developed through residencies including O k’inādās Residency, The Banff Musicians in Residence Program, and Territ-Aur(i)al Imprints Exchange thanks to the 2016 Artist Fellowship grant from the Arrowhead Regional Arts Council.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

When Rivers Were Trails: Cultural Expression in an Indigenous Video Game - LaPensée, Elizabeth (International Journal of Heritage Studies, 2021)
When Rivers Were Trails is a 2D adventure game wherein The Oregon Trail meets Where the Water Tastes Like Wine through an Indigenous lens. The game depicts a myriad of cultures during the player’s journey from Minnesota to California amidst the impact of land allotment in the 1890s. Initiated by the Indian Land Tenure Foundation, the game was developed in collaboration with the Games for Entertainment and Learning Lab at Michigan State University thanks to support from the San Manuel Band of Mission Indians and the many Indigenous creatives who contributed design, art, music, and writing. Uniquely, When Rivers Were Trails is a sovereign game, meaning that it was directed and informed by Indigenous creatives who maintained the role of final decisions during development. Merging design research and close reading methods, this study sets out to describe the game’s design, development process in regards to the game writing, and the resulting themes which emerged as a result of engaging Indigenous writers in self-determined representations.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

A Pedestal, A Table, A Love Letter: Archaeologies of Gender in Videogame History - Nooney, Laine (Game Studies, 2013)
The history of videogames has largely been imagined as a patrilineal timeline. Women, when they emerge as participants in the game industry, are typically figured as outliers, exceptions, or early exemplars of “diversity” in the game industry. Yet the common practice of “adding women on” to game history in a gesture of inclusiveness fails to critically inquire into the ways gender is an infrastructure that profoundly affects who has access to what kinds of historical possibilities at a specific moment in time and space. This contribution aims to shift the relevant question from “Where are women in game history?” to “Why are they there in the way that they are?” To do so, the essay strategically deploys Sierra On-Line co-founder and lead designer Roberta Williams as an exceptional case study on the problem of gender in videogame history. Drawing from both media archaeology and feminist cultural studies, this contribution first outlines the function Roberta Williams serves as a gendered subject of game history. The remainder of the essay is organized as three short, non-chronological vignettes about specific objects and practices in the biography of Roberta Williams. Attention to the contextual specificity of Roberta Williams and her historical moment produces an alternative genealogy for gaming centered around relations of intimacy and labor in domestic space. Rather than producing a chronology, the method of this essay illustrates a historical critique by sketching a contour that unsettles the presumptive logic of what we must account for when we write about the objects and subjects of game history.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Arts of engagement: taking aesthetic action in and beyond the Truth and Reconciliation Commission of Canada - Martin, Keith; Robinson, Dylan (Indigenous studies series, 2016)
It's about the role that music, film, visual art, and Indigenous cultural practices play in and beyond Canada's Truth and Reconciliation Commission on Indian Residential Schools. The essays question the ways in which components of the reconciliation, such as apology and witnessing, have social and political effects for residential-schools survivors, intergenerational survivors, and settler publics."-- Provided by publisher
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Género, representación y nuevas tecnologías: mujeres y video en México - Pech, Cynthia (Revista mexicana de ciencias políticas y sociales, 2006)
En este artículo, se aborda la temática del video como tecnología de género. El video es el medio de creación artística que algunas mujeres están utilizando para crear lo que se puede llamar imá genes en femenino. Se hace un acercamiento al discurso feminista y los presupuestos teóricos que se han tomado para el análisis del discurso videográfico de las mujeres. Se presenta un breve análisis de los trabajos de las videastas Pola Weiss y Pilar Rodríguez.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-TV; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créatrice; _Nettoyé

L'Oeil amérindien: regards sur l'animal - Dionne, Hélène (Éditions du Septentrion, 1991)
Cette publication a été réalisée à l'occasion de l'exposition "L'Oeil Amérindien, Regards sur l'Animal au Musée de la civilisation à Québec.
Keywords: 1-Histoire de l'art; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Exposer, diffuser, faire entendre sa voix: présence de l'art contemporain autochtone au Québec entre 1967 et 2013 - De Lacroix, Pricile (Université du Québec à Montréal, 2017)
Ce mémoire se penche sur la diffusion de l'art contemporain autochtone au Québec de 1967 à 2013. Grâce à un corpus constitué de 640 expositions comprenant au moins un artiste des Premières Nations, métis ou inuit s'étant tenues quelque part dans la province à l'intérieur de ces 46 années, il a été possible de dresser un portrait global raisonné de ce qui s'est fait – ou ne s'est pas fait – concrètement, au-delà des a priori maintes fois reconduits. Il démontre, par exemple, que la décennie 1990 n'a pas été si « désertique » qu'il n'y parait, mais que la période 2000-2013, malgré son apparente vigueur, cache plusieurs dynamiques à l'œuvre au Québec rendant la reconnaissance et l'intégration des artistes autochtones dans le grand réseau des arts contemporains encore difficile. Ce mémoire apporte un éclairage sur le rôle marquant joué par les réseaux parallèles dans la diffusion de l'art contemporain autochtone, celui, parfois novateur, joué par les musées d'histoire et d'ethnographie ainsi que par les musées au sein même des communautés autochtones, puis la fermeture bien visible des institutions d'art du Québec jusqu'au milieu des années 2000. Il met également en lumière la présence de solitudes existantes au Québec, c'est-à-dire celle qui opère une division entre les artistes autochtones francophones et anglophones, favorisant grandement ces derniers, ainsi qu'entre artistes autochtones versus allochtones, les deux se mélangeant encore difficilement au sein des expositions. Enfin, ce mémoire permet de constater qu'en quatre décennies, le nombre d'artistes autochtones pratiquant de manière professionnelle au Québec n'a cessé d'augmenter, que Montréal s'est inscrite de plus en plus comme une métropole pouvant attirer des artistes autochtones de calibre national et international, que certaines régions du Québec, comme le Saguenay et l'Abitibi, ont, contrairement à d'autres, fait preuve d'une ouverture certaine face à l'art autochtone, mais également qu'il y a eu – et qu'il y a peut-être encore – une corrélation entre événements festifs et expositions accrues d'art contemporain autochtone, ce qui a tendance à le garder dans le domaine du folklore au Québec, et nuire véritablement à la reconnaissance des artistes professionnels.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Baliser le territoire: a stake in the ground : Manifestation d'art contemporain autochtone - Myre, Nadia (Les Éditions Art Mûr, 2012)
Catalogue d'exposition. Du 14 janvier au 25 février 2012 à Art Mûr (Montréal. Titre : Baliser le territoire : Manifestation d’art contemporain autochtone / A Stake in the Ground: Contemporary Native Art Manifestation. Commissaire : Nadia Myre Sonny Assu, Jason Baerg, Carl Beam, Rebecca Belmore, Kevin Lee Burton, Hannah Claus, Bonnie Devine, Raymond Dupuis, Edgar Heap of Birds, Vanessa Dion Fletcher, Nicholas Galanin, Greg Hill, Robert Houle, Maria Hupfield, Rita Letendre, Glenna Matoush, Alan Michelson, Nadia Myre, Marianne Nicolson, Michael Patten, Arthur Renwick, Sonia Robertson, Greg Staats, Tania Willard, Will Wils
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le ré-ensauvagement par l’art: Le vieil Indien, les pommes rouges et les Chasseurs-Chamanes-Guerriers - Sioui Durand, Guy (Captures, 2018)
L’article part de la notion wendat d’ohtehra’ pour développer une approche de l’art contemporain autochtone comme processus de « ré-ensauvagement » à l’œuvre, entre autres, chez les artistes Kent Monkman (Cri-Irlandais) et Caroline Monnet (Anishinaabe-Française). L’auteur, en s’appuyant sur les théoriciens Deborah Doxtator (Kanien’kehá:ka), Georges Emery Sioui (Wendat) et Taiaiake Alfred (Kanien’kehá:ka) propose également une analyse de l’autochtonie en Amérique du Nord comme un fait glocal d’Américité.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sakahàn: art indigène international - Hill, Greg A.; Lalonde, Christine.; Hopkins, Candice (Musée des beaux-arts du Canada, 2013)
Sakahàn' celebrates a growing international commitment to the collection, study and exhibition of indigenous art. Featuring more than 75 artists from around the world, this remarkable project places indigenous art squarely at the centre of contemporary art produced today.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Indigenous Art: New Media and the Digital - Igloliorte, Heather; Nagam, Julie; Taunton, Carla (Public : art, culture, ideas, 0845-4450 ; volume 27, issue 54, 2016)
Indigenous Art New Media and the Digital convenes leading scholars, curators, and artists from the Indigenous territories in Canada, the United States of America, Australia, and Aotearoa (New Zealand). It brings forth urgent conversations about resistance to colonial modernism, and highlights the historic and ongoing use of technology by Indigenous communities and artists as vehicles of resilience and cultural continuity. This issue ignites productive dialogue around the definitions of new and digital media art and practice-based work within the framework of Indigenous art and theory
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Call it a Vision Quest : Machinima in a First Nations context - Lapensée, Elizabeth; Lewis, Jason E. (Understanding Machinima Essays on Filmmaking in Virtual Worlds, 2013)
Article sur les machinimas de l'artiste Skawennati (Kanien'kehá:ka) et du travail du laboratoire d'ABTEC (Aboriginal Territories on cyberspace) à l'Université Concordia.
Keywords: 1-Histoire de l'art; 2-Recherche-création; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À vérifier-Jeu vidéo

Transference, Tradition, Technology: Native New Media Exploring Visual & Digital Culture - Townsend, Melanie A.; Hopkins, Candice (Walter Phillips Gallery Editions, 2005)
Transference, Tradition, Technology explores Canadian Aboriginal new media and references the work of artists within a political, cultural and aesthetic milieu. The book constructs a Native art history relating to these disciplines, one that is grounded in the philosophical and cosmological foundations of Aboriginal concepts of community and identity within the rigour of contemporary arts discourse. Approachable in nature but scholarly in content, this book is the first of its kind. A text book for students and teachers of Canadian Aboriginal history and visual and media art, and a source for writers, scholars and historians, Transference, Tradition, Technology is co-produced with the Art Gallery of Hamilton, Hamilton; and Indigenous Media Arts Group, Vancouver.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“I Want to Call Their Names in Resistance”: Writing Aboriginal Women into Canadian Art History. - Farrell Racette, Sherry (Rethinking Professionalism: Essays on Women and Art in Canada, 1850-1970, 2012)
As bell hooks points out in “Aesthetic Inheritances: History Worked by Hand,” writing an inclusive art history is no easy task. Until very recently, Aboriginal women have been written out of Canadian art history, or rather art history has been written around us. How do we write ourselves in? It falls far beyond simple insertion; the erasures are far too deep. Insertion presumes a simple forgetfulness, an oversight, a neglecting of the obvious. Insertion assumes a presence. It implies a shared mode of history, a common belonging to a collective archive, and an agreed-upon understanding of what it means to be an artist. Beyond the important considerations of race, gender, culture, and social class, our distinct legal status in Canada must be acknowledged. This was particularly true for women artists working between 1880 and 1970. For much of the time period under consideration, First Nations communities lived under a profoundly restrictive regime of colonial power. Relationships between First Nations people and the Canadian state have been defined by the Indian Act, a piece of legislation enacted in 1876 and surviving, through many amendments and revisions, until the present time.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art in our Lives native Women Artists in Dialogue - Chavez Lamar, Cynthia; Farrell Racette, Sherry; Evans, Lara (School for Advanced Research Press, 2010)
The culmination of three seminars at SAR's Indian Arts Research Center (IARC) that brought together Native women artists to discuss the balancing of their art practice with the myriad roles, responsibilities, and commitments they have. The artworks were diverse in media and content and are featured in the plates section of this volume, along with the artist statements that accompanied the pieces in the exhibit. The chapters reflect some of the seminars emerging themes: gender, home/crossing, and art as healing/art as struggle
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Close Encounters: The Next 500 Years - Farrell Racette, Sherry. (Plug In Editions., 2011)
Catalogue d'exposition publié à l'occasion de l'exposition tenue au Plug In Institute of Contemporary Art, Urban Shaman Contemporary Aboriginal Art, et Winnipeg Art Gallery, du 22 janvier au 8 mai 2011. Now is the moment to reconfigure our notions of time to reveal alternative ways of thinking and being for the future. In Close Encounters: The Next 500 Years Indigenous artists imagine the future within the context of present experiences and past histories. By radically reconsidering encounter narratives between native and non-native people, Indigenous prophecies, possible utopias and apocalypses, this exhibition proposes intriguing possibilities for the next 500 years. "We all in different measure have carved out the future," observes Hopi photographer and filmmaker, Victor Masayesva, in his book Husk of Time. "We are all clairvoyants, soothsayers, prophets, knowingly assuming our predictions. Close Encounters brings together over 30 Indigenous artists from across Canada, the United States, South America, Europe, Australia and New Zealand, including newly commissioned work from Rebecca Belmore, Faye HeavyShield, Kent Monkman, and Edward Poitras. Jimmie Durham's sculptural work A Pole to Mark the Centre of the World (at Winnipeg) will be an ongoing critique of widely held ideas surrounding space and location, while James Luna's poignant installation The Spirits of Virtue and Evil Await my Ascension, addresses issues of ritual and the passing of time. Close Encounters showcases artists and artworks that collectively invent provocative futures from a diversity of perspectives and practices. With its myriad histories, trajectories, tensions, collisions, and self-image(s), the city of Winnipeg offers an intriguing juxtaposition for these artistic mediations. Close Encounters: The Next 500 Years presents international Indigenous perspectives in a city that in many ways also epitomizes the future of Aboriginal people in Canada. Works in multiple venues throughout the city will serve as catalysts to invent different ways of thinking, acting, and being in the world of our shared future. At this pivotal moment in time, Close Encounters invites engagement with the speculative, the prophetic, and the unknown
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Trickster Shift: Humour and Irony in Contemporary Native Art - Ryan, Allan J. (University of British Columbia Press, 1999)
The influence of the "trickster" in contemporary Canadian native art is entwined with cultural sensibilities and expressed through ironic humour. Exploring the trickster's presence, this text allows the artists to offer their own ideas on the creative process and the nature of native humour.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé